Effect of a prospective payment method for health facilities on direct medical expenditures in a low-resource setting: a paired pre-post study. Issue 7 (4th June 2020) - Meda, Ivlabèhiré Bertrand; Kouanda, Seni; Dumont, Alexandre; Ridde, Valéry
Abstract: Almost all sub-Saharan countries have adopted cost-reduction policies to facilitate access to health care. However, several studies underline the reimbursement delays experienced by health facilities, which lead to deficient implementation of these policies. In April 2016, for its free care policy, Burkina Faso shifted from fee-for-service (FFS) paid retrospectively to FFS paid prospectively. This study tested the hypothesis that this new method of payment would be associated with an increase in direct medical expenditures (expenses covered by the policies) associated with deliveries. This paired pre-post study used data from two cross-sectional national surveys. Observations were paired according to the health facility and the type of delivery. We used a combined approach (state and household perspectives) to capture all direct medical expenses (delivery fees, drugs and supplies costs, paraclinical exam costs and hospitalization fees). A Wilcoxon signed-rank test was used to test the hypothesis that the 2016 distribution of direct medical expenditures was greater than that for 2014. A total of 279 pairs of normal deliveries, 66 dystocia deliveries and 48 caesareans were analysed. The direct medical expenditure medians were USD 4.97 [interquartile range (IQR): 4.30–6.02], 22.10 [IQR: 15.59–29.32] and 103.58 [IQR: 85.13–113.88] in 2014 vs USD 5.55 [IQR: 4.55–6.88], 23.90 [IQR: 17.55–48.81] and 141.54 [IQR: 104.10–172.02] in 2016 for normal, dystocia and caesarean deliveries, respectively. Except for dystocia ( P  = 0.128) and medical centres ( P  = 0.240), the 2016 direct medical expenditures were higher than the 2014 expenses, regardless of the type of delivery and level of care. The 2016 expenditures were higher than the 2014 expenditures, regardless of the components considered. In the context of cost-reduction policies in sub-Saharan countries, greater attention must be paid to the provider payment method and cost-control measures because these elements may generate an increase in medical expenditures, which threatens the sustainability of these policies.